Wind induced coastal erosion in Peninsular Malaysia - Ramesh, Yanalagaran (2017)
Malaysia has a long coast line which is about 4809km; with 29% undergoing coastal erosion. These coastlines are important because they are economical center for agriculture, aquaculture, oil and gas exploitation and etc. Coastal erosion is a natural phenomenon mainly caused by wind-wave motion. The direction of wave depends on the direction of the wind flow which is called the Wind-wave relationship. This research was conducted to study the relationship of wind and wave in accordance to the coastal erosion phenomena. The erosion location was compared with two years of shoreline changes which is from 1984 to 2016. The erosion was determined by the visibility of erosion in all the research location. Visible erosion shows a large displacement of land which is due to the natural geomorphology process and non-visibility shows the absence of erosion which might be due to land reclamation over the years. The wind direction distribution was created using the significant wind data for each erosion location. Both this information was analyzed and it results in providing a significant relationship of wind-wave and coastal erosion. Theoretically, the wind direction is directly proportional to the erosion direction. As such, the regression analysis of wind direction versus erosion direction produces a directly proportional graph with a value of R²=0.8638 @ 0.9 for this research. In conclusion, this research proves that wind direction can be used to determine the erosion direction for future research.